Flexural strengthening of steel I-beams by using CFRP strips - Narmashiri, K.; Ramli Sulong, Nor Hafizah; Jumaat, Mohd Zamin (International Journal of Physical Sciences, 2011)
This paper presents the experimental and numerical studies on the carbon fibre reinforced polymer (CFRP) flexural strengthened steel I-beams. Eight steel beams were carefully chosen with the same length and different types and thicknesses of CFRP plates. Both experimental test and numerical simulation were employed. In the experimental test, the gradual static loading in four-points bending method was utilized. In numerical simulation, ANSYS software in the three dimensional (3D) modeling case and nonlinear static analysis method were employed. Results show that different types and thicknesses of CFRP plates influenced the failure modes, load capacities, and strain distributions on the CFRP plates.